2019
DOI: 10.1002/ccd.28302
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous axillary artery approach for ductal stenting in critical right ventricular outflow tract lesions in the neonatal period

Abstract: Objectives We aimed to assess the experience using a percutaneous axillary artery approach for insertion of arterial ductal stents in patients with critical right ventricular outflow tract lesions at two tertiary pediatric cardiology centers. Background Patent ductus arteriosus stenting is an accepted palliative alternative to BT shunts for neonates with critical right heart lesions. Access to tortuous ductus' may be challenging via the femoral artery, whereas the carotid artery presents a low risk of stroke. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…35,36 It may also ease wire and catheter exchanges, which can be critical in cases of hemodynamic instability or other complications. 38 In addition, Bauser-Heaton et al 36 found that the flip technique was associated with shorter procedure times for highly tortuous PDAs, although this did not reach statistical significance. Although the distance to the patient's airway can pose challenges to the anesthesiology team, it does allow for easy access to lower extremity lines, and the benefits of the overall procedure likely outweigh this difficulty.…”
Section: Vascular Approachmentioning
confidence: 98%
See 4 more Smart Citations
“…35,36 It may also ease wire and catheter exchanges, which can be critical in cases of hemodynamic instability or other complications. 38 In addition, Bauser-Heaton et al 36 found that the flip technique was associated with shorter procedure times for highly tortuous PDAs, although this did not reach statistical significance. Although the distance to the patient's airway can pose challenges to the anesthesiology team, it does allow for easy access to lower extremity lines, and the benefits of the overall procedure likely outweigh this difficulty.…”
Section: Vascular Approachmentioning
confidence: 98%
“…Although there is a paucity of large-scale data on vascular access for PDA stenting, multiple smaller observational studies present promising outcomes for the carotid and axillary arteries, particularly for approaching vertical PDAs through the superior aspect of the aortic arch. 25,30,[35][36][37][38][39][40][41] Bauser-Heaton et al 36 observed that carotid and axillary artery access is more commonly used in highly tortuous PDAs than the femoral artery and that procedural and late complications were similar regardless of the access site. Similarly, Alsawah et al 37 reported that percutaneous carotid access was more commonly used in complex ductal anatomy, and they found that both immediate access-related complications and delayed local complications in these cases were significantly lower than in cases that used the femoral artery.…”
Section: Vascular Approachmentioning
confidence: 99%
See 3 more Smart Citations